In vitro Antimicrobial and Antioxidant Activity of Meliaceae Plants Collection of Eka Karya Bali Botanic Garden - Arrohmatus Syafaqoh Li’aini; I Putu Agus Hendra Wibawa; Ayyu Rahayu (Molekul, 2022)
Meliaceae are popularly used to produce terpenoid and limonoid compounds. These compounds have the potential as antioxidants, antimicrobials, insecticides, antipyretics, and anthelmintics. This research aims to determine the antioxidant and antimicrobial activity of Meliaceae leaves extract of Eka Karya Bali Botanic Garden plants collection. The dried leaves of 15 species of Meliaceae were extracted by methanol. In vitro antimicrobial tests were carried out on agar media inoculated by selected microbe. On the other hand, the antioxidant activity was assayed by 1,1-diphenyl-2-picryl hydrazyl (DPPH) radical scavenging. As a result, Aphanamixis polystachya against Aspergillus niger (35.21 mm) and Cladosporium sp. (46.21), Toona hexandra against Fusarium solani (37.31 mm), Dysoxylum cauliflorum against Candida albicans (38.19 mm), Chisocheton pentandrus against Salmonella typhimurium (39.53 mm), Sandoricum koetjape against Staphylococcus aureus (50.07 mm), and Toona hexandra against Streptococcus nutans (42.25 mm) exhibited the strongest inhibitory effect. Furthermore, the antioxidant screening showed that Cipadessa baccifera, C. pentandrus, and Sandoricum koetjape exhibited strong antioxidant activity, while T. ciliata showed a very strong antioxidant activity with IC50 33.64 μg/mL. This study reveals an initial screening of the potential of various types of Meliaceae as a source of antioxidants and antibacterials. Furthermore, this information can be used as a new alternative for pharmaceutical companies and the industrial sector in the development of new products.